Brush-like polymer electrolyte, controllable preparation method and application

The polymers with specific structures are synthesized through controlled radical polymerization technology and effectively combined with other components, which solves the problem of polymer electrolyte structure regulation, realizes the preparation of high-performance solid electrolytes, and improves the electrochemical performance and safety of the battery.

CN119812455APending Publication Date: 2025-04-11ZHEJIANG XINAN CHEM IND GRP CO LTD +1

Patent Information

Application Number
CN202411981546.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

How to accurately regulate the polymer structure of polymer electrolytes, achieve ideal ion conductivity and mechanical strength, and solve the leakage risks, poor thermal stability and flammability of traditional liquid electrolytes.

Method used

Polymers with specific structures, such as brush-like polymers, are synthesized by controlled radical polymerization technology, and effectively combine them with other electrolyte components through specific preparation processes to form high-performance solid electrolytes.

Benefits of technology

The chain structure of polymer electrolyte is accurately and controllable, which significantly improves the electrochemical performance of the battery, including improving ionic conductivity, voltage windows and mechanical strength, and enhancing the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812455A_ABST
    Figure CN119812455A_ABST
Patent Text Reader

Abstract

The invention discloses a brush-like polymer electrolyte, a controllable preparation method and application, and relates to the field of battery electrolyte materials. The controllable preparation method of the brush polymer electrolyte comprises the following steps: (1) uniformly mixing an acrylate monomer containing unsaturated double bonds, a molecular weight regulator, a plasticizer and metal salt to obtain a precursor solution; (2) adding an initiator into the precursor solution obtained in the step (1), and uniformly mixing to obtain an electrolyte solution; and (3) injecting the electrolyte solution obtained in the step (2) into the battery, and curing to obtain a finished battery. The polymer electrolyte with an accurate and controllable chain structure is obtained by regulating and controlling a substituent group structure, molecular weight size and distribution, a topological structure and the like in a polymer chain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery electrolyte materials, and in particular to a brush-like polymer electrolyte, a controllable preparation method and an application thereof. Background Art

[0002] With the increasing global demand for clean energy and efficient energy storage technology, the performance optimization of energy storage devices has become an important topic in scientific research and industry. Traditional liquid electrolytes have been widely used in lithium-ion batteries, but their inherent leakage risk, poor thermal stability and flammability limit the safety and service life of the batteries. Therefore, solid electrolytes, especially polymer electrolytes, are regarded as ideal candidate materials for the next generation of energy storage devices with high energy density, long service life and high safety performance due to their light weight, good flexibility, structural designability and higher interface compatibility.

[0003] The core advantage of polymer electrolytes is that the physicochemical properties of electrolytes can be adjusted through molecular design to meet the needs of different energy storage devices. However, how to precisely regulate the polymer structure of polymer electrolytes to achieve ideal ionic conductivity and mechanical strength is a major challenge in current polymer electrolyte research. Controlled radical polymerization (CRP) technology provides a solution to this problem. CRP technology allows researchers to precisely control the molecular weight, molecular weight distribution and topological structure of polymers at the molecular level, which is crucial to improving battery performance. Polymers synthesized by CRP technology, such as block copolymers, star polymers, hyperbranched polymers and brush polymers, can not only effectively reduce the glass transition temperature of the material and increase the amorphous region, but also significantly improve the segment motion and ion transport capacity of the polymer electrolyte, thereby optimizing the electrochemical performance of the battery.

[0004] Although CRP technology has brought revolutionary breakthroughs to the development of polymer electrolytes, there are still many technical obstacles to overcome before this technology can be applied to actual production. For example, how to efficiently and economically synthesize polymers with specific structures, and how to effectively combine these polymers with other components of the electrolyte (such as lithium salts, matrix materials, etc.) to form high-performance solid electrolytes are both hot spots and difficulties in current research.

[0005] In the prior art, the patent application with publication number CN113471531A proposes an innovative polymer solid electrolyte and its preparation method, as well as a solid-state battery based on the electrolyte. The polymer solid electrolyte combines a plant cellulose aerogel matrix, a comb-shaped PEO-based polymer and a lithium salt, and achieves the dual advantages of high ionic conductivity and excellent mechanical strength through a specific preparation process. Among them, the plant cellulose aerogel matrix not only provides a stable structural support for the electrolyte, but also promotes the rapid transmission of lithium ions through its porous structure; the comb-shaped PEO-based polymer effectively improves the chain segment movement and ion conductivity of the electrolyte through its special molecular structure; the lithium salt, as the active ingredient in the electrolyte, ensures the normal charging and discharging process of the battery.

[0006] The preparation method of this patent application describes in detail the process from the dissociation and functionalization of plant cellulose, to the preparation of aerogel, to the synthesis of comb-shaped PEO-based polymers, and the final electrolyte mixing, filling and curing process. Each step has been carefully designed to ensure the optimal performance of the final product. For example, in the dissociation process of plant cellulose, high-quality nano-plant cellulose can be obtained by controlling the reaction conditions and purification methods; in the functionalization step, the compatibility of cellulose with polymers and lithium salts is improved by introducing specific functional groups; in the synthesis of comb-shaped PEO-based polymers, polymer molecules with specific structures are obtained by precisely controlling the proportion of raw materials and reaction conditions; in the final mixing, filling and curing process, the uniform distribution and close combination of the various components of the electrolyte are achieved by optimizing the process parameters.

[0007] In summary, as one of the key materials for solid-state batteries, the optimization of polymer electrolyte performance is of great significance to improving the overall performance of the battery. Synthesizing polymers with specific structures through controlled free radical polymerization technology and effectively combining polymers with other components using innovative preparation processes are important directions in current polymer electrolyte research. Summary of the invention

[0008] The present invention aims to provide a brush-like polymer electrolyte, a controllable preparation method and application, and obtain a polymer electrolyte with a precisely controllable chain structure by regulating the substituent structure, molecular weight size and distribution, topological structure, etc. in the polymer chain.

[0009] In order to achieve the above-mentioned purpose, the technical solution of the present invention is as follows:

[0010] In one aspect, the present invention provides a controllable preparation method of a brush-like polymer electrolyte, comprising the following steps:

[0011] (1) uniformly mixing an acrylate monomer containing an unsaturated double bond, a molecular weight regulator, a plasticizer, and a metal salt to obtain a precursor solution;

[0012] (2) adding an initiator to the precursor solution obtained in step (1), and mixing them uniformly to obtain an electrolyte solution;

[0013] (3) Injecting the electrolyte solution obtained in step (2) into the battery and solidifying it to obtain a finished battery.

[0014] Specifically, in step (1), the acrylic acid ester monomer containing an unsaturated double bond is at least one compound having a structure as shown in Formula I,

[0015]

[0016] In formula I, R1 is hydrogen or methyl, and R2 is at least one of formula II,

[0017]

[0018] In formula II, n is an integer from 1 to 20;

[0019] Specifically, in step (1), the molecular weight regulator is at least one of dithiocarbonate and trithiocarbonate,

[0020] The structural formula of the dithiocarbonate is shown in Formula III,

[0021]

[0022] The structural formula of the trithiocarbonate is shown in Formula VI,

[0023]

[0024] wherein R and Z each represent an alkyl group or an aryl group.

[0025] Preferably, the molecular weight regulator is at least one of S,S-dibenzyl trithiocarbonate, 2-phenyl-2-propylbenzodisulfide, S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester, 2,2′-[methylthiobis(thio)]bis[2-methylpropionic acid], benzyl dithiobenzoate, carbazole-9-dithiobenzyl ester, 3-(((benzylthio)carbonylthio)thio)propionic acid, 4-cyano-4-[[(dodecylthio)carbonylthio]thio]pentanoic acid, and 4-cyanopentanoic dithiobenzoic acid.

[0026] Specifically, in step (1), the plasticizer is at least one of succinonitrile, acetonitrile, tetrahydrofuran, ethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane;

[0027] The metal salt includes a lithium salt, a sodium salt or a potassium salt, wherein the lithium salt is at least one of LiPF6, LiTFSI, LiFSI, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiCl and LiI; the sodium salt is at least one of NaPF6, NaCF3SO3, NaFSI, NaTFSI, NaBF4, NaBOB, NaDFOB and NaClO4; the potassium salt is at least one of KBF4, KClO4, KPF6, KFSI and KTFSI.

[0028] The initiator is at least one of an azo compound and an organic peroxide. In the embodiment of the present invention, the azo compound can be selected from one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate initiators, and the organic peroxide can be selected from one of benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.

[0029] The molar ratio of the molecular weight regulator to the acrylic ester monomer containing unsaturated double bonds is 1:20-100, the added amount of the initiator is 0.05%-5% of the mass of the acrylic ester monomer containing unsaturated double bonds, the plasticizer accounts for 10%-50% of the total mass of the electrolyte solution, and the metal salt accounts for 5%-30% of the total mass of the electrolyte solution.

[0030] Preferably, the curing temperature in step (3) is 40 to 100° C. and the curing time is 2 to 24 hours.

[0031] On the other hand, the present invention also provides a brush-like polymer electrolyte prepared by the controllable preparation method.

[0032] The invention also provides application of the brush-like polymer electrolyte in preparing metal ion batteries.

[0033] The present invention also provides a metal ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte uses the brush-like polymer electrolyte.

[0034] Beneficial effects of this application:

[0035] The present application provides a controllable preparation method and use of a brush-like polymer electrolyte, which can obtain a polymer electrolyte with a precisely controllable chain structure by regulating the substituent structure, molecular weight size and distribution, topological structure, etc. in the polymer chain. By precisely regulating the chemical structure, sequence structure, and topological structure of the polymer electrolyte, controllable regulation of battery performance can be achieved to develop a polymer electrolyte system that meets practical application requirements (such as ionic conductivity, voltage window, and mechanical strength, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a photograph of a brush-like polymer electrolyte provided in Example 1 and Comparative Examples 1-3 of the present application.

[0037] Figure 2 This is a low-field nuclear magnetic resonance spectrum of a brush-like polymer electrolyte provided in Example 1 and Comparative Examples 1-3 of the present application.

[0038] Figure 3 This is a low-field nuclear magnetic resonance spectrum of a brush-like polymer electrolyte provided in Example 1 and Comparative Examples 4-5 of the present application. DETAILED DESCRIPTION

[0039] The technical solution provided by the embodiment of the present invention is to solve the above technical problems, and the overall idea is as follows:

[0040] In a first aspect, an embodiment of the present application provides a controllable preparation method of a brush-like polymer electrolyte, wherein the brush-like polymer electrolyte comprises an acrylate monomer containing an unsaturated double bond, a molecular weight regulator, a lithium salt, and a plasticizer;

[0041] The embodiment of the present application provides a controllable preparation method of a brush-like polymer electrolyte, which includes acrylate as a monomer and dithiocarbonate or trithiocarbonate as a molecular weight regulator, which can effectively regulate the distribution and content of the solvent in the polymer chain, the substituent structure, the molecular weight and distribution, the topological structure, etc., to obtain a polymer with a precisely controllable chain structure. When applied to solid electrolyte materials such as lithium batteries, it can effectively solve the problem of regulating the electrochemical properties of polymer electrolytes such as ionic conductivity, voltage window, and mechanical strength.

[0042] As an implementation method of an example of the present application, the molar ratio of the monomer to the molecular weight regulator is 1:(20-100).

[0043] In the present application, the role of controlling the molar ratio of the monomer to the molecular weight regulator to 1:(20-100) is to ensure successful regulation of the polymer chain structure so that the reaction proceeds fully and the resulting brush-like polymer electrolyte has controllable electrochemical properties.

[0044] As an implementation method of the present application, the reaction temperature is 40-100° C. and the reaction time is 2-24 hours.

[0045] In the present application, the role of controlling the reaction temperature and time is to ensure the occurrence of the polymerization reaction and to allow the reaction to proceed fully.

[0046] In a second aspect, an embodiment of the present application provides a controllable preparation method of an electrolyte using the brush polymer described in the first aspect, the preparation method comprising:

[0047] (1) uniformly mixing a monomer, a molecular weight regulator, a plasticizer, and a metal salt to obtain a precursor solution;

[0048] (2) adding an initiator to the precursor solution obtained in step (1), and mixing them uniformly to obtain an electrolyte solution;

[0049] (3) Injecting the precursor solution obtained in step (2) into the battery.

[0050] (4) After the battery is assembled, it is heated and allowed to stand. Under the action of the initiator, the acrylic ester monomers in the electrolyte solution polymerize inside the battery to obtain a brush-like polymer electrolyte.

[0051] The controllable preparation method of the brush-like polymer electrolyte provided in the embodiment of the present application is simple to operate, does not require additional specific equipment, and can achieve mass production.

[0052] In the present application, in some specific embodiments, due to different chemical structures of molecular weight regulators, different monomers, different molar ratios of monomers and molecular weight regulators, different plasticizers, initiators and metal salts, and different reaction temperatures and times, the product brush-like polymer electrolytes have different chemical structures, sequence structures and topological structures.

[0053] In a third aspect, an embodiment of the present application provides a metal ion battery, the battery comprising:

[0054] The electrolyte of the second aspect,

[0055] Negative pole, and positive pole.

[0056] In the present application, the metal ion battery can be prepared in the following manner.

[0057] First, prepare a positive electrode. A positive electrode active material or a positive electrode active substance, a conductive agent, a binder, and a solvent may be mixed together to prepare a positive electrode material composition. The positive electrode material composition may be directly coated on an aluminum current collector to prepare a positive electrode plate having a positive electrode material film. In some embodiments, the metal organic coordination polymer may be cast on a separate carrier to form a positive electrode active material film. The positive electrode active material film may then be separated from the carrier and laminated on an aluminum current collector to prepare a positive electrode plate (or positive electrode) having the positive electrode active material film.

[0058] Next, the negative electrode may be prepared as follows. The negative electrode may be prepared in the same manner as applied to the positive electrode, except that a negative electrode active material is used instead of the positive electrode active material. Conductive agents, binders and solvents that can be used to prepare the negative electrode active material composition may be the same as those used to prepare the positive electrode.

[0059] For example, a negative electrode active material, a conductive agent, a binder, and a solvent may be mixed together to prepare a negative electrode active material composition. The negative electrode active material composition may be directly coated on a copper current collector to prepare a negative electrode plate (or negative electrode). In some embodiments, the negative electrode active material composition may be cast on a separate carrier to form a negative electrode active material film. The negative electrode active material film may then be separated from the carrier and laminated on a copper current collector to prepare a negative electrode plate.

[0060] Next, the brush-like polymer electrolyte may be prepared as described in the second aspect.

[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then proceed according to general international standards, conventional conditions, or according to the conditions recommended by the manufacturer.

[0062] Example 1

[0063] The preparation of the brush-like polymer electrolyte comprises the following steps:

[0064] 10g polyethylene glycol methyl ether methacrylate (M n ~500g mol -1 , n=9), 3.2g succinonitrile and 2.87g LiTFSI, stirred at room temperature for 1h to obtain a clear, transparent colorless solution, 0.12g S,S-dibenzyl trithiocarbonate and 0.01g azobisisobutyronitrile were added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then allowed to stand at 80°C for 24h to polymerize to obtain a brush-like polymer electrolyte.

[0065] In order to verify the precise control of the length of the main chain of the molecular weight regulator brush polymer electrolyte and its effect on the electrolyte properties, the following comparative experiments were conducted:

[0066] Comparative Example 1

[0067] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.01 g of azobisisobutyronitrile was added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then allowed to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0068] Comparative Example 2

[0069] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.06 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then left to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0070] Comparative Example 3

[0071] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.03 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dropped onto the diaphragm during the assembly of button cells in a glove box. The battery was then left to stand at 80 °C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0072] The polymerization effect diagram of the brush-like polymer electrolyte obtained in Example 1 and Comparative Examples 1-3 is shown in FIG. Figure 1 As shown in FIG. 1 , all four groups of experiments can obtain solid polymer electrolytes. The brush-like polymer electrolytes obtained in Example 1 and Comparative Examples 1-3 were subjected to low-field nuclear magnetic resonance detection, and the corresponding spectra are shown in FIG. Figure 2 shown. Figure 2 The results show that with the introduction of molecular weight regulators, the proportion of solvent in the crystalline region (T2 = 1-10ms) continues to decrease until it is almost gone, while the content of solvent in the amorphous region continues to increase, which can effectively promote the conduction of lithium ions.

[0073] In order to verify the precise regulation of the molecular weight regulator on the length of the brush polymer electrolyte side chains and the effect on the electrolyte properties, the following comparative examples were made:

[0074] Comparative Example 4

[0075] 15 g of polyethylene glycol methyl ether methacrylate (n=15), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.12 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then allowed to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0076] Comparative Example 5

[0077] 20 g of polyethylene glycol methyl ether methacrylate (n=20), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.12 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dropped onto the diaphragm during the assembly of button cells in a glove box. The battery was then allowed to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0078] The brush-like polymer electrolytes obtained in Example 1 and Comparative Examples 4-5 were subjected to low-field nuclear magnetic resonance detection, and the corresponding spectra are shown in FIG. Figure 3 shown. Figure 3 The results show that when the number of main chain units remains the same, the longer the side chain length, the greater the proportion of solvent in the crystalline region (T2 = 1-10ms), which is not conducive to the conduction of lithium ions.

[0079] Example 2

[0080] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.6 g of ethylene glycol dimethyl ether and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.12 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then left to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0081] Example 3

[0082] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 5.74 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.12 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisobutyronitrile were added, and then dropped onto the diaphragm during the assembly of button cells in a glove box. The battery was then left to stand at 80°C for 24 h to polymerize to obtain a brush-like polymer electrolyte.

[0083] Example 4

[0084] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.1 g of benzyl dithiobenzoate and 0.01 g of azobisisobutyronitrile were added, and then dripped onto the diaphragm during the assembly of button cells in a glove box, and the battery was then placed at 80°C for 24 h to polymerize to obtain a brush polymer electrolyte.

[0085] Example 5

[0086] 10 g of polyethylene glycol methyl ether methacrylate (n=9), 3.2 g of succinonitrile, and 2.87 g of LiTFSI were stirred at room temperature for 1 h to obtain a clear, transparent, colorless solution, 0.12 g of S, S-dibenzyl trithiocarbonate and 0.01 g of azobisisoheptonitrile were added, and then the solution was dropped onto the diaphragm during the assembly of button cells in a glove box. The battery was then allowed to stand at 60°C for 12 h to polymerize to obtain a brush-like polymer electrolyte.

[0087] Test Example 1

[0088] (1) Ionic conductivity: A steel-on-steel symmetrical cell was tested using a Bio-logic VPM-300 electrochemical workstation in the frequency range of 7 MHz to 0.1 Hz and at 30 °C to obtain the ionic conductivity σ = L / RS, where σ is the ionic conductivity, L is the thickness of the electrolyte membrane, R is the electrolyte resistance, and S is the effective electrode surface area.

[0089] (2) Electrochemical window: Stainless steel was used as the working electrode and lithium metal was used as the reference electrode. Linear voltammetry was performed on a Chenhua 760E electrochemical workstation with a test range of 0.0 V to 8.0 V and a scan rate of 5 mV / s.

[0090] Table 1

[0091] Group Ionic conductivity (S cm-1) Electrochemical Window (V) Example 1 <![CDATA[1.21×10 -3 ]]> 4.7 Comparative Example 1 <![CDATA[2.03×10 -4 ]]> 4.9 Comparative Example 2 <![CDATA[6.52×10 -4 ]]> 4.8 Comparative Example 3 <![CDATA[8.49×10 -4 ]]> 4.7 Comparative Example 4 <![CDATA[1.17×10 -4 ]]> 4.9 Comparative Example 5 <![CDATA[8.36×10 -5 ]]> 5.0

[0092] The experimental data obtained from the test are shown in Table 1. The more the molecular weight regulator amount is, the higher the ionic conductivity of the polymer electrolyte is and the narrower the electrochemical window is; the longer the polymer brush chain is, the lower the ionic conductivity of the polymer electrolyte is.

Claims

1. A controllable preparation method of a brush-like polymer electrolyte, characterized in that: The following steps are involved: (1) uniformly mixing an acrylate monomer containing an unsaturated double bond, a molecular weight regulator, a plasticizer, and a metal salt to obtain a precursor solution; (2) adding an initiator to the precursor solution obtained in step (1), and mixing them uniformly to obtain an electrolyte solution; (3) Injecting the electrolyte solution obtained in step (2) into the battery and solidifying it to obtain a finished battery.

2. The controllable preparation method of the brush-like polymer electrolyte according to claim 1, characterized in that: In step (1), the acrylic ester monomer containing an unsaturated double bond is at least one compound having a structure as shown in Formula I, In formula I, R1 is hydrogen or methyl, and R2 is at least one of formula II, In formula II, n is an integer of 1-20.

3. The controllable preparation method of the brush-like polymer electrolyte according to claim 1, characterized in that: In step (1), the molecular weight regulator is at least one of a dithiocarbonate and a trithiocarbonate, The structural formula of the dithiocarbonate is shown in Formula III, The structural formula of the trithiocarbonate is shown in Formula IV, Here, R and Z each represent an alkyl group or an aryl group.

4. The controllable preparation method of the brush-like polymer electrolyte according to claim 3, characterized in that: The molecular weight regulator is at least one of S,S-dibenzyl trithiocarbonate, 2-phenyl-2-propylbenzodisulfide, S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonyl ester, 2,2′-[methylthiobis(thio)]bis[2-methylpropionic acid], benzyl dithiobenzoate, carbazole-9-dithiobenzyl ester, 3-(((benzylthio)carbonylthio)thio)propionic acid, 4-cyano-4-[[(dodecylthio)carbonylthio]thio]pentanoic acid, and 4-cyanopentanoic dithiobenzoic acid.

5. The controllable preparation method of the brush-like polymer electrolyte according to claim 1, characterized in that: In step (1), the plasticizer is at least one of succinonitrile, acetonitrile, tetrahydrofuran, ethylene glycol dimethyl ether, 1,3-dioxolane, and 1,4-dioxane; The metal salt is a lithium salt, a sodium salt or a potassium salt; The lithium salt is at least one of LiPF6, LiTFSI, LiFSI, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiCl, and LiI; the sodium salt is at least one of NaPF6, NaCF3SO3, NaFSI, NaTFSI, NaBF4, NaBOB, NaDFOB, and NaClO4; the potassium salt is at least one of KBF4, KClO4, KPF6, KFSI, and KTFSI; The initiator is at least one of an azo compound and an organic peroxide.

6. The controllable preparation method of the brush-like polymer electrolyte according to claim 1, characterized in that: The molar ratio of the molecular weight regulator to the acrylic acid ester monomer containing unsaturated double bonds is 1:20-100. The amount of the initiator added is 0.1%-5% of the mass of the acrylic ester monomer containing unsaturated double bonds. The plasticizer accounts for 10%-50% of the total mass of the electrolyte solution. The metal salt accounts for 5%-30% of the total mass of the electrolyte solution.

7. The controllable preparation method of the brush-like polymer electrolyte according to claim 1, characterized in that: The curing temperature in step (3) is 40 to 100° C. and the curing time is 2 to 24 hours.

8. A brush-like polymer electrolyte prepared by the controllable preparation method according to any one of claims 1 to 7.

9. Use of the brush-like polymer electrolyte according to claim 8 in the preparation of metal ion batteries.

10. A metal ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the brush-like polymer electrolyte according to claim 8.

Citation Information

Patent Citations

  • Polymer solid electrolyte, preparation method thereof and solid-state battery

    CN113471531A

Cited By

  • High-voltage-resistant polymer solid electrolyte as well as preparation method and application thereof

    CN121394554A